A review on genetic transformation protocols of tomato (Solanum lycopersicon) / Nurul Afiqah Md Yusop - Md Yusop, Nurul Afiqah (Faculty of Plantation and Agrotechnology, 2019)
Tomato, scientifically named (Solanum lycopersicon L.) is one of the most essential vegetable crops and a model plant to study other plants. For further study in biotechnology especially for basic and practical studies for tomato improvement, successful transformation is important. However, the success of genetic manipulation of a plant depends on the transformation as well as regeneration frequencies of the explants. So, the purpose of this study was to assess and compare different transformation protocols in tomato. Transformation of cotyledonary leaf explant was successfully performed with gene transfer into tomato by Agrobacterium tumefaciens mediated transformation and efficiency. Frequency of transient and stable transformation has been identify and showed that the transformation competence in tomato was highly influenced by several factors. There are eight factors affecting the efficiency of tomato transformation including genotypes, explant type, agrobacterium strains, explant size, explant orientation on medium, co-cultivation period, pre-culture of explant and kanamycin concentration tolerance test for selection of transformed tissue. All these factors along with kanamycin concentration will determine the successful of genetic in tomato. Besides, previous study had revealed that 200 mg/l kanamycin is optimum for selection of transformed explant. This review also discovered that, in-vitro fruit injection (in-planta transformation) method is more efficient compared to conventional tissue culture based transformation methods.